SEPSIS RISK FACTORS IN ELDERLY PATIENTS AT ROYAL PRIMA MEDAN GENERAL HOSPITAL - Bagas Dwi Sanjaya; Michelle Hendriani Djuang; Fazwiansyah Darlin Muniro; Linda Chiuman (Universitas Negeri Gorontalo, 2022)
Abstract Sepsis is a severe infectious disease accompanied by the discovery of a systemic response that can include hypothermia, hyperthermia, tachycardia, hyperventilation, and fatigue. Some studies suggest age is the most common risk factor for sepsis. The goal of the study was to determine the risk factors for sepsis in elderly patients associated based on age, gender, diagnosis, location of the infection, and length of treatment. The study used 100 samples of elderly patients aged 60 years diagnosed with sepsis. Descriptive analysis techniques with cross-sectional designs are used to explain the characteristics of each research variable. The results of the study explained that the risk factors for sepsis most in elderly patients by age are 70 years as many as 53 people (53.0%), female sex as many as 52 people (52.0%), endocrinological diagnoses as many as 24 people (23.5%), the location of lung infections as many as 20 people (19.6%), the length of treatment 3 to 7 days as many as 45 people (45%). Based on the results of the study showed that the elderly are an age that is susceptible to sepsis because the immune system and organ function will decrease with age. Endocrine diseases, such as diabetes mellitus, and infections of the lungs are the biggest risk factors for sepsis in the elderly.